Effect of peat decomposition and mass loss on mistoric mercury records in peat bogs from Patagonia - Biester, Harald; Kilian, Rolf (Environmental science & technology, 2003)
Ombrotrophic peat bogs have been widely used to evaluate long-term records of atmospheric mercury (Hg) deposition. One of the major aims of these investigations is the estimation of the increase in atmospheric Hg fluxes during the industrial age compared to preindustrial fluxes. Comparability of Hg accumulation rates calculated from density, peat accumulation rates, and Hg concentrations requires linearity between these parameters. Peat formation is a dynamic process accompanied by intense mass loss and alteration of the organic material. Our investigations on three peat cores from the Magellanic Moorlands, Chile, indicate that Hg concentrations in peat strongly depend on peat humification. Moreover, differences in mass accumulation rates during peat evolution are not compensated by linear changes in density, peat accumulation, or Hg concentrations. We suggest that Hg accumulation rates be normalized to carbon accumulation rates to achieve comparability of Hg accumulation rates derived from differently altered peat sections. Normalization to the carbon accumulation rates reduces Hg accumulation rates in less degraded peat sections in the upper peat layers by factors of more than 2. Our results suggest that the increase in Hg deposition rates during modern times derived from ombrotrophic peat bogs are potentially overestimated if Hg accumulation rates are not corrected for mass accumulation rates.